The Influence of Competence and Work Motivation on Employee Performance of PT PAL Indonesia - Ahmad Yanuar Bahri; Indah Respati Kusumasari; Budi Prabowo; Rusdi Hidayat Nugroho (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine the effect of competence and work motivation on employee performance at PT PAL Indonesia. The research method used is a quantitative approach with a sample of 92 employees selected through proportional stratified random sampling. Data analysis techniques employ multiple linear regression with t-test and F-test for hypothesis testing. The results show that competence and work motivation have a positive and significant effect on employee performance, both partially and simultaneously. The coefficient of determination (R²) value of 54.3% indicates that competence and work motivation contribute significantly to improving employee performance, while the remaining percentage is influenced by other factors. These findings emphasize the importance of competence development and motivation improvement to support optimal employee performance.